Autosomal recessive chondrodysplasia with severe short stature caused by a biallelic COL10A1 variant. Issue 6 (22nd August 2017) - Ain, Noor ul; Makitie, Outi; Naz, Sadaf
Abstract : Background: Heterozygous mutations in COL10A1 underlie metaphyseal chondrodysplasia, Schmid type (MCDS), an autosomal dominant skeletal dysplasia. Objective: To identify the causative variant in a large consanguineous Pakistani family with severe skeletal dysplasia and marked lower limb deformity. Methods: Whole exome sequencing was completed followed by Sanger sequencing to verify segregation of the identified variants. In silico variant pathogenicity predictions and amino acid conservation analyses were performed. Results: A homozygous c.133 C>T (p.Pro45Ser) variant was identified in COL10A1 in all six severely affected individuals (adult heights 119–130 cm, mean −6.33 SD). The individuals heterozygous for the variant had mild phenotype of short stature (adult heights 140–162 cm, mean −2.15 SD) but no apparent skeletal deformities. The variant was predicted to be pathogenic by in silico prediction tools and was absent from public databases and hundred control chromosomes. Pro45 is conserved in orthologues and is located in the non-collagenous 2 domain of COL10A1, variants of which have never been associated with skeletal dysplasia. Conclusions: This first report of individuals with a homozygous variant in COL10A1 defines a new type of autosomal recessive skeletal dysplasia. The observations in COL10A1 variant carriers suggest a phenotypic overlap between the mildest forms of MCDS and idiopathic short stature.